Cultivating an Entrepreneurial Mindset in Student Entrepreneurs as a Foundation for Becoming New Business Owners - Rizky F, R. Mochamad Daud (CV. Tripe Konsultan, 2026)
This study aims to analyze the importance of fostering an entrepreneurial mindset among university students as an initial step in creating new entrepreneurs. Entrepreneur students are individuals who are not only academically oriented but also possess the ability to identify opportunities, innovate, and take risks in business activities. This study employs a qualitative approach using a literature review method based on various relevant scientific sources. The results indicate that the development of an entrepreneurial mindset is influenced by internal factors such as motivation and mindset, as well as external factors including educational environment and social support. Entrepreneur students play a strategic role as potential new entrepreneurs, as they already possess practical experience, managerial skills, and readiness to face business risks. In conclusion, the development of an entrepreneurial mindset during university education is a key factor in increasing the number of new entrepreneurs and supporting national economic growth.